Peran Akal Menurut Pandangan Al-Ghazali - Fuadi Fuadi (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
Intellect is a tool of thought contained in human beings, the human mind is different from other creatures because sense is given only in humans and is not given to other creatures. This difference has made humans superior and smarter in managing their lives. Therefore man with a clear intellect would find God as the final returns from real life. According to al-Ghazali sense a profound effect on the human mind even define perfection the man himself. Al-Ghazali in principle recognize the existence of the senses and the intellect, but both instruments are limited and may not be essential to understand the science. Al-Ghazali argued that scientific truth is not limited to sensory truth, but there is truth behind the truth abstract sense. Al-Ghazali had divided power in some sense be viewed by potential and levels: first, practical sense; sense it serves to move the body and to deliver knowledge-practical knowledge, such as the application of morals in life. Second, Intellect theoretical; theoretical sense is the power of knowledge in human beings or the desire to know that is immaterial and abstract